Knowledge, attitude and treatment seeking behaviour among postmenopausal women in an urban slum area of Bhubaneswar, Odisha - Kumari, Amrita; Panda, Meely; Das, Sai Chandan (International Journal Of Community Medicine And Public Health, 2019)
Background: In every women life this unique physiological phase that is menopause take place. In developing countries like in India most of women neglected their basic health care which poses the major public health challenges. The objectives of the study were to assess the knowledge, attitude towards menopause and its associated factors among postmenopausal women of urban slum; to explore the treatment seeking behaviour and the barriers for not seeking health care among these post-menopausal women. Methods: This cross sectional study was conducted using multistage cluster sampling and house to house visit in randomly selected slums under the UHTC area of KIMS, Bhubaneswar. A pretested and predesigned questionnaire was used among 220 postmenopausal women. Results: The results of the study show that 60.9% of women have a heard about menopause before attaining menopause but 33.1% women attitude towards menopause is negative. Only 10% of study population were aware of HRT that it treats menopausal symptoms. We found that the awareness of cancer cervix was 19.1% but the screening was done only by 2.7% of study population. Conclusions: There is considerably lack of knowledge and awareness about the effects and the treatment of menopausal symptoms especially in rural and slum women in India. So, such studies help in creating awareness since disseminating health education for postmenopausal women is of prime importance.